Perspektywy i wyzwania. Współpraca Chin i Polski w obszarze kształcenia zawodowego w kontekście VET 4.0 .......... 321 - Cui, Xiaojing (70 lat polonistyki Pekińskiego Uniwersytetu Języków Obcych: Dziedzictwo, rozwój, innowacje, 2025)
PROSPECTS AND CHALLENGES OF CHINA-POLAND VOCATIONAL EDUCATION COOPERATION IN THE CONTEXT OF VET 4.0Poland has a long history of vocational education and a mature training system, and is actively advancing the process of Vocational Education and Training (VET) 4.0, aimed at Industry 4.0. In recent years, Chinese colleges such as Cangzhou Technical College in Hebei have been actively cooperating with Polish colleges like the University of Applied  Sciences in Wałcz and University of Łódź in areas such as cooperation in running schools, teacher exchanges, student exchanges, and academic cooperation, to cultivate internationally skilled specialists. In the context of VET 4.0, there are vast opportunities for cooperation between China and Poland in accelerating the digital transformation of vocational education. However, facing challenges arising from differences in culture, language, education systems, policies and laws, it is still necessary to think about how to establish effective communication and support mechanisms, align with the latest strategies and policies for the development of vocational education, and explore new cooperation potential in vocational education and training in fields like artificial intelligence and other information technologies.